Bộ soạn thảo sơ đồ logic sched trên máy vi tính IBM-PC - Duc, Dang Van (Journal of Computer Science and Cybernetics, 2018)
The article refer to SCHED system, a logic capture for logic simulation. It deals with schematics library organization, draw’s scheduler and an algorithm for translating from schema in to netlist.